2015
DOI: 10.1051/0004-6361/201425420
|View full text |Cite
|
Sign up to set email alerts
|

EVN observations of 6.7 GHz methanol maser polarization in massive star-forming regions

Abstract: Context. Theoretical simulations and observations at different angular resolutions have shown that magnetic fields have a central role in massive star formation. Like in low-mass star formation, the magnetic field in massive young stellar objects can either be oriented along the outflow axis or randomly. Aims. Measuring the magnetic field at milliarcsecond resolution (10-100 au) around a substantial number of massive young stellar objects permits determining with a high statistical significance whether the dir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 77 publications
(120 reference statements)
4
24
0
Order By: Relevance
“…4) and it is consistent with the strength of our measured polarisation fraction (e.g. Surcis et al 2015).…”
Section: Strength Of the Magnetic Fieldsupporting
confidence: 91%
See 3 more Smart Citations
“…4) and it is consistent with the strength of our measured polarisation fraction (e.g. Surcis et al 2015).…”
Section: Strength Of the Magnetic Fieldsupporting
confidence: 91%
“…Previous works showed that the circular polarisation fraction in methanol masers is typically very weak (<1%; e.g Surcis et al 2015), so circular polarisation can be observed more easily in the brightest maser features. However, as shown by Vlemmings et al (2001Vlemmings et al ( , 2002, an increase of the noise, a narrowing and re-broadening, or a change in shape of the maser line can also occur in hyperfine interactions or in 3D maser propagation effect.…”
Section: Strength Of the Magnetic Fieldmentioning
confidence: 98%
See 2 more Smart Citations
“…Cyganowski et al (2011a) resolved five distinct sources at 3.6 cm (denoted CM1,..., CM5). The two strongest (CM1 and CM2) were also detected by these authors at 1.3 cm, and CM2 is associated with 6.7 GHz CH 3 OH masers (Cyganowski et al 2009(Cyganowski et al , 2011aSurcis et al 2015). The morphology of the 1.3 cm continuum emission in our VLA image is consistent with multiple, unresolved centimeter sources, and is spatially coincident with CM1, CM2, CM4, and CM5 from Cyganowski et al (2011a).…”
Section: Notes On Individual Sourcessupporting
confidence: 86%